Karakteristik Pasien Apendisitis di RSUD Dr. H. Abdul Moeloek - Fitria, Aghniya Rizqy; Ricky Ramadhian, Muhammad; Daulay, Suryani Agustina; Zuraida, Reni (CV. Jasa Sukses Abadi, 2025)
Appendicitis is inflammation of the vermiform appendix that can lead to perforation if not treated promptly. This study aims to identify the characteristics of appendicitis patients at RSUD Dr. H. Abdul Moeloek Lampung Province from January 2023 to July 2024. The method used was a descriptive observational study using secondary data from medical records of appendicitis patients. The sample was taken using total sampling, which was then selected based on inclusion and exclusion criteria, involving 84 patients with complete medical records and histopathology results. The results showed that the majority of appendicitis patients were in the 21-60 age range (49%), followed by the 0-20 age range (44%) and the >60 age group (7%). Based on gender, more male patients (56%) were found compared to females (44%). The most common type of appendicitis was simple acute appendicitis (48.8%), followed by perforated acute appendicitis (36.9%) and chronic appendicitis (14.3%). These findings are consistent with other studies showing a higher incidence of appendicitis in young adults and a higher prevalence in males. This study provides important insights into the characteristics of appendicitis patients, which may aid in early detection and more effective management.